Application and exploration of total hip arthroplasty for developmental dysplasia of the hip assisted by full-process robotics - Hongxin Shi; Rao Yu; Luqiao Pu; Baochuang Qi; Cheng Meng; Junxiao Ren; YongQing Xu; Chuan Li (BMC Musculoskeletal Disorders)
Abstract Objective This study aimed to explore whether total hip arthroplasty (THA) aided by full-process robotics was effective in patients undergoing developmental dysplasia of the hip (DDH). Methods Totally 112 patients were enrolled and classified into robotic-assisted group (n = 56) and the conventional group (n = 56). In addition, retrospective analysis was used for comparing the difference in therapeutic efficacy. Results A total of 112 patients received THA, and were followed up for (12.78 ± 0.76) months on average, with no occurrence of associated complications. For patients in robot-assisted group, their abduction and anteversion angles of acetabular cup placement were in the safe zone, while those in 8 patients of the conventional group were outside the safe zone. Compared to the conventional group, the robot-assisted group had higher postoperative Harris Hip Score and FJS, whereas lower VAS score. Conclusion Robot-assisted THA is advantageous in terms of both intraoperative precision and postoperative effect on the treatment of patients with DDH.